Analysis of User Satisfaction with the Cards Application Using the End User Computing Satisfaction Method - Eldita, Xenaya Hawa; Safitri, Sisilia Thya; Setyadi, Resad (Journal of INISTA, 2024)
The rapid development of technology has significantly facilitated daily activities and brought about numerous changes in society. This swift technological advancement has had a profound impact on the development of payment systems in transactions. Various applications like CARDS have become well-known and widely utilized by many individuals to streamline their day-to-day transactions. CARDS application is also popular within school environments, making it easier for students and cooperative employees to conduct transactions for purchasing food, beverages, and other school necessities. However, there are challenges that need to be addressed regarding the use of the CARDS application. One of them is the lack of understanding among some parents in operating the application and loading credits. End User Computing Satisfaction can be used as a method to measure the level of satisfaction of a system application's users. This method compares user expectations with the reality provided by the application, thereby identifying how well the application meets user expectations. The research results will provide recommendations for improving the application, taking into account the End User Computing Satisfaction method.